Comparison of classification techniques to review the plausibility of adjustments to multiples-based equity valuations : empirical study for South Africa - Gouws, Jauné (Stellenbosch : Stellenbosch University, 2022)
Thesis (MCom)--Stellenbosch University, 2022.